Zmienne w relacjach politycznych Unii Europejskiej z Egiptem po roku 2012 - Przybylska-Maszner, Beata (Rocznik Integracji Europejskiej, 2015)
The paper attempts to indicate the variables that define the framework of EU policy towards Egypt in 2012–2014, and to analyse the scope of the new approach to mutual relations in terms of politics. Particular attention is given to the mechanism of various instruments applied by different EU policies and their implementation in the context of political developments in Egypt. These considerations allow the author to draw conclusions on the future possibilities for the European Union to continue its activities within the framework of cooperation in Egypt, taking into consideration the necessity to agree on common interests and to implement an adopted stand- point.